REGIONAL DIFFERENTIATION OF POLISH TOURISM ECONOMY WITHIN 2002–2008 - Zbigniew Binderman; Bolesław Borkowski; Wiesław Szczesny (Acta Scientiarum Polonorum. Oeconomia, 2010)
Conducted research has shown an improvement in the level of tourism availability in Poland during the studied period. An average level of tourism (defined as an annual average from 16 voivodeships) rose during the studied period by nearly 70%, which gives an average annual growth of 9%. It is worth to note that this growth was significantly larger during 2005–2008 than during 2002–2005. In a regional perspective those changes are not uniform. Regional differentiation of voivodeships during a given year, measured by a coefficient of variation, decreased visibly by 16%. Radar methods employed in the research turned out to be very useful in the analysis of the studied phenomenon. Radar methods, modified by the authors, can be employed on a wider scale, for example, because of, easy multidimensional data visualization. In the next stage we anticipate the creation of an user friendly computer package.